Significance of erythropoesis correction in preoperative preparation in the surgical treatment of patients with colorectal cancer - Novikov, S.P.; Poliiants, A.V.; Tverdokhlib, I.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Anemic syndrome, which accompanies the development of pathology in patients with colorectal cancer, can cause serious early postoperative complications. The question of how preoperative preparation activities influence the state of the intestinal structures and the clinical situation in general is relevant. Of particular importance in this situation is the correction of anemic syndrome before surgery, using hematopoietic stimulants. Objective. The purpose of the study is to analyze the dynamics of erythropoiesis and changes in tissue and cell ultrastructure in intraoperative colon biopsy specimens after stimulation of erythropoiesis in preoperative preparation in the surgical treatment of patients with colorectal cancer. Methods. The study of red bone marrow and the wall of the large intestine using transmission electron microscopy. Results. Most patients with colorectal cancer are characterized by the development of signs of ineffective erythropoiesis with a moderate slowdown in the differentiation of erythroblasts and a delay in the release of mature erythrocytes into the systemic circulation. Stimulation of erythropoiesis with the help of epoetin leads to an increase in the functional activity of the central macrophages of the erythropoietic islets of the red bone marrow and the enhancement of their intercellular association with maturing erythroid cells. This is accompanied by the formation of a large number of full-fledged erythrocytes, an increase in the numerical density of cells of the erythroid series and the normalization of their ultrastructure. Conclusion. Stimulation of erythropoiesis with the help of epoetin in the preoperative period causes the inhibition of endothelial dysfunction due to the restriction of dystrophic and destructive changes in endothelial cell organelles, stabilization of their membranes, prevention of arteriole spasm, erythrocyte stasis and erythrocyte phenomena. As a result, the phenomena of infiltration, perivascular and interstitial edema in the composition of the membranes of the intestinal wall are much less pronounced than in the group of patients without preoperative activation of erythropoiesis.